The Nahdlatul Ulama's Contribution to Peacemaking in A Digital Era - Setia, Paelani; Rahim, Rahimin Affandi Abdul (Hanifiya: Jurnal Studi Agama-Agama, 2024)
This research discusses the role of Nahdlatul Ulama (NU) in promoting peace in the digital era. In its background, digitization has fundamentally altered the paradigm of human communication and interaction. This study aims to analyze NU's practices in promoting peace and tolerance in the digital world and to identify the challenges and opportunities faced by NU in this regard. The research method used is a qualitative approach with online observation and content analysis of materials produced and disseminated by NU on social media and other digital platforms. The results show that NU actively advocates messages of peace and tolerance through direct activities and inclusive digital content production. NU also engages in interfaith dialogue and cross-religious cooperation in the digital world. Despite receiving positive responses from the public, NU also faces challenges and controversies, such as the emergence of misleading content on social media, the presence of controversial figures affiliated with NU, and the disagreement over the term â€œIslam Nusantara.â€ This research argues that NU plays a crucial role in introducing peace through the virtual world, with significant contributions to understanding the role of religion in the digital era and developing more effective strategies in leveraging digital technology for peace purposes.